2017
DOI: 10.23876/j.krcp.2017.36.4.318
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of arteriovenous fistula: Analysis of key factors

Abstract: The growing proportion of individuals suffering from chronic kidney disease has considerable repercussions for both kidney specialists and primary care. Progressive and permanent renal failure is most frequently treated with hemodialysis. The efficiency of hemodialysis treatment relies on the functional status of vascular access. Determining the type of vascular access has prime significance for maximizing successful maturation of a fistula and avoiding surgical revision. Despite the frequency of arteriovenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 92 publications
(92 reference statements)
1
66
0
7
Order By: Relevance
“…According to the literature, variables such as age, educational level, diabetes, peripheral vascular disease, hypertension, coagulopathy, obesity, and smoking affect AVF maturation time and hematoma formation 7,8,[11][12][13][14] . Consistent with our results, Lee et al (2006) 11 prospectively studied AVF infiltration in the United States and found no association of sex, race, and diabetes with occurrence of hematomas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the literature, variables such as age, educational level, diabetes, peripheral vascular disease, hypertension, coagulopathy, obesity, and smoking affect AVF maturation time and hematoma formation 7,8,[11][12][13][14] . Consistent with our results, Lee et al (2006) 11 prospectively studied AVF infiltration in the United States and found no association of sex, race, and diabetes with occurrence of hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD, conventional hemodialysis can be performed through different types of vascular access, including central venous catheter and arteriovenous fistula (AVF) 7 . An AVF consists of a subcutaneous anastomosis between an artery and an adjacent vein, with dilation of superficial veins, allowing constant circulation and repeated needle insertion 8,9 .…”
Section: Medeiros Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Hal ini berbeda dengan acuan pustaka lainnya yang menyatakan bahwa faktor risiko seperti penyakit kardiovaskular, hiperlipidemia, dan hipertensi dapat menurunkan kemungkinan menjadi maturnya suatu AVF, dengan asumsi terjadinya disfungsi endotel pada penyandang hipertensi. 12 Hiperurisemia merupakan salah satu komorbid yang diamati pada penelitian ini mengingat cukup tinggi jumlah pasien PGK dengan komorbid ini Hal ini sesuai dengan acuan pustaka yang menyatakan bahwa hiperurisemia mempunyai hubungan erat dangan angka kejadian PGK tahap akhir. 13 Pada penelitian ini didapatkan 25 pasien (61%) yang menyandang hiperurisemia, dan terdapat 23 pasien dengan AVF yang menjadi matur, dan hanya 2 pasien dengan AVF yang tidak matur.…”
Section: Gambar 3 Sebaran Data Bfr Intraoperasi Dan 6 Mingguunclassified